A Note on the Accurate Computation of Structural Properties for Dynamic Control Systems. Issue 20 (2022) - Stigter, J.D.; Joubert, D.; van Willigenburg, L.G.; Molenaar, J.
Abstract: In analysing the observability, identifiability, and controllability of smooth (possibly non-linear) dynamic control systems, the authors identified numerous ways to improve both the accuracy and efficiency of their computations. We summarize a few techniques that help to pinpoint exactly what kind of linear dependencies exist between parametric output sensitivities. These relations, in turn, can be traced back with the help of computer algebra software to an exact re-parametrizations of the original model. The suggested techniques to increase the accuracy of results will be presented on the basis of a few examples.